Hungarian Monitoring, 17 October 1988 . [Magyar rádiófigyelő], 1988. október 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports on the Yugoslav Party Central Committee meeting - Arbatov article in Pravda on the disarmament talks - Statement on the Polish government session - Largest ever credit agreement approved between USSR and FRG - Article exposes Stakhanovism in Komsomolskaya Pravda Domestic Affairs: - Whitehead's visit to Budapest - Secretary of state Imre Miklós discusses in the Vatican Pope's visit to Hungary, appointing assistant bishops, minority rights and freedom of religion - János Kádár receives Indian Congress Party delegation - Israeli minister for industry and trade in talks with Tamás Beck and industry minister Frigyes Berecz - Hungarian delegation led by Ferenc Kárpáti travels to Prague for Warsaw Pact defense ministers' committee meeting - Libraries' sequestered materials - Ethnographic conference begins in Eger on the situation of Hungarians living beyond the borders, their living conditions Economy: - First Hungarian computing industry exhibition opens - On the experiences of the first Hungarian concern: report on Medicor - Why does the Bükkabrány lignite power station need to be built? Külpolitika: - Tudósítások a jugoszláv párt KB üléséről - Arbatov cikk a Pravdában a leszerelési tárgyalásokról - Jelentés a lengyel kormány üléséről - Jóváhagyták a SZU és az NSZK közti legnagyobb hitel megállapodást - Leleplező cikk a sztahanovizmusról a Komszomolszkaja Pravdában Belpolitika: - Whitehead budapesti látogatása - A pápa magyarországi látogatásáról, segédpüspökök kinevezéséről, a kisebbségi jogról és a vallásszabadságról tárgyalt a Vatikánban Miklós Imre államtitkár - Kádár János fogadta az indiai kongresszus párt küldöttségét - Az izraeli ipari és kereskedelmi miniszter Beck Tamással és Berecz Frigyes ipari miniszterrel tárgyalt - Kárpáti Ferenc vezetésével magyar küldöttség utazott Prágába a VSZ honvédelmi miniszteri bizottságának ülésére - A könyvtárak zárolt anyaga - A határon kívül élő magyarság helyzetéről, életkörülményeiről kezdődött néprajzi konferencia Egerben Gazdaság: - Megnyílt a hazai számítógépipar első szakkiállítása - Az első magyar konszern tapasztalatairól: riportműsor a Medicorról - Miért van szükség a bükkábrányi lignit erőmű felépítésére?